2022
DOI: 10.3390/ijerph192315482
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal Regional Spontaneous Neural Activity and Functional Connectivity in Unmedicated Patients with Narcolepsy Type 1: A Resting-State fMRI Study

Abstract: Background: Previous Resting-state functional magnetic resonance imaging (fMRI) studies have mainly focused on cerebral functional alteration in processing different emotional stimuli in patients with narcolepsy type 1 (NT1), but were short of exploration of characteristic brain activity and its remote interaction patterns. This study aimed to investigate the spontaneous blood oxygen fluctuations at rest and to elucidate the neural mechanisms underlying neuropsychiatric behavior. Method: A total of 18 unmedica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 47 publications
0
2
0
Order By: Relevance
“…In contrast to these findings, however, a substantial corpus of research reports diminished cortical thickness, reduced glucose metabolism, and lower ALFF values in the prefrontal cortex of narcolepsy patients (Joo et al, 2009;Kim et al, 2009;Dang-Vu, 2013;Wada et al, 2019;Cavaliere et al, 2020;Jeon et al, 2020;Wu et al, 2022). These conflicting results may stem from methodological differences in neuroimaging techniques, including changes in data acquisition, preprocessing, analysis, and even patient status during scanning.…”
Section: Increase In Rsfc In Narcolepsymentioning
confidence: 94%
See 1 more Smart Citation
“…In contrast to these findings, however, a substantial corpus of research reports diminished cortical thickness, reduced glucose metabolism, and lower ALFF values in the prefrontal cortex of narcolepsy patients (Joo et al, 2009;Kim et al, 2009;Dang-Vu, 2013;Wada et al, 2019;Cavaliere et al, 2020;Jeon et al, 2020;Wu et al, 2022). These conflicting results may stem from methodological differences in neuroimaging techniques, including changes in data acquisition, preprocessing, analysis, and even patient status during scanning.…”
Section: Increase In Rsfc In Narcolepsymentioning
confidence: 94%
“…Previous studies based on sMRI, fMRI, DTI, and PET/CT have yielded conflicting results ( Dang-Vu, 2013 ; Cavaliere et al, 2020 ). A large number of structural nuclear magnetic resonance and functional magnetic resonance studies in resting state and task state have proved that the thickness and volume of prefrontal cortex decreased ( Joo et al, 2009 ; Kim et al, 2009 ; Jeon et al, 2020 ), the intensity of functional connection decreased ( Wu et al, 2022 ), and the activity of low frequency amplitude decreased ( Fulong et al, 2018 ), and it was related to clinical features, including cognitive, memory and emotional abnormalities ( Engström et al, 2014 ; Huang et al, 2016 ; Cavaliere et al, 2020 ), which was supported by the hypometabolism of prefrontal cortex shown by PET/CT ( Huang et al, 2018 ). However, the research field is not always consistent.…”
Section: Introductionmentioning
confidence: 99%